ANALISIS VEGETASI DI KAWASAN AGROWISATA GUNUNG TUMPA - Faris Andong; Fabiola B. Saroinsong; Alfonsius Thomas; Wawan Nurmawan (Universitas Sam Ratulangi, 2015)
ABSTRACT VEGETATION ANALYSIS IN AGROWISATA AREA OF MOUN TUMPA This study was to determine the composition and structure of plants in the Region Agro Mount Tumpa. The methods used sguare line with a line. Plot size of 2 m × 2 m for seedling phase, 5 m × 5 m for phase stake, 10 m × 10 m to 20 m mast and phase × 20 m for phase tree. There are 15 plots in three transect observations were cut lengthwise contour lines, the distance between plots of 50 m, and the distance between lines of 100 m. Observation data trunk diameter of 130 cm height from ground level, the name of plant species and number of individuals per species. To obtain the importance value index is calculated density, dominance, and frequency. Based on the results, 40 species and 29 families of trees in the phase of the tree, tree, saplings and seedlings. Of the highest importance value index of tree species Spathodea campanulata phase with (IVI 59,00%), in the phase of pole types which have the highest importance value index Artocarpus altilis types have the (IVI 44.52%), type that have the highest importance value index of phase stake is Piper aduncum with (IVI 37.17%). As for the types that have the highest IVI seedling phase is kind Adenostoma viscosum with (IVI 76.19%). Keywords: Important Value Index, Analysis Vegetation Agrowista Mountain Region Tumpa.